Karakterisasi Isolat-isolat Beauveria Bassiana Galur Lokal Sulawesi Selatan - Rachmawaty (Bionature, 2008)
Beauveria mildew is known as useful natural control agent, due to it’s infection potential agents for controlling insect. The range of its host covers broad range of insects order including Lepidoptera, Coleoptera, Hemiptera and Hymenoptera. In the past, the behavior of B.bassiana was identified based on morphological character, which is have weakness because of environmental effect so the fenotype performance does not manifest the genotype value. Another identification method can be used to complete morphological approach is identification based on physiological behavior (toxin production) and biochemical (protein and isoenzim) where the protein analysis and isoenzim, is order to minimize the influence of environment factor for identification. The research was conducted in Laboratorium Biology UNM, there is 11 isolates B.bassiana used in this research represent location and host. Isolates were analyzed by physiological and isoenzim using electrophoresis. The result of physiological character showed that out of 11 isolates characterized, there are isolates produced beauvericin, interestingly the rest isolates produced unknown on identified metabolites. Based on total band protein pattern and isoenzim showed that there are variation, isolates from the same area or district have more similarity characters than isolates from different area.